A head-to-head comparison of poly(sarcosine) and poly(ethylene glycol) in peptidic, amphiphilic block copolymers. (12th June 2015) - Huesmann, David; Sevenich, Adrian; Weber, Benjamin; Barz, Matthias
Abstract: In this work we compare chemical and solution properties, like critical aggregate concentrations (CAC) and hydrodynamic radii of aggregates based on either poly(ethylene glycol) or poly(sarcosine) block copolymers in aqueous solution. The amine functionalized, hydrophilic polymers poly(sarcosine) (degree of polymerization, Xn  = 100 and 200) and PEG (Xn  = 121 and 242) of comparable hydrodynamic volume were used to initiate the ring opening polymerization of α-amino acid- N -carboxyanhydrides based on ɣ-benzyl-l -glutamate (Glu(OBn)) or ε-carboxybenzyl-l -lysine (Lys(Z)). The second, hydrophobic block was kept at a degree of polymerization of 25 and 50 to enable a direct comparison of solution properties of block copolymers. In both cases block length could be precisely adjusted and all synthesized block copolymers have narrow molecular weight distributions and dispersities between 1.1 and 1.2. Both types of block copolymers display critical aggregate concentrations in the range of 6*10 −8 –3*10 −7  mol/L and aggregates possess hydrodynamic radii in a range of 40–100 nm. PEG based systems, however, have a slightly lower CAC and tend to form smaller micelles, while PSar based systems have commonly smaller μ2 parameter indication more uniform aggregates. Graphical abstract: Highlights: PSar and PEG based block copolymers can be synthesized in a controlled manner. PSar and PEG display comparable hydrodynamic volumes for Xn around 100 and 200. CMCs of PSar and PEG based block copolymers are comparable. PEG242 -or PSar202 -block-PGlu(OBn)50 form micelles while others yield more complex aggregates.